A systematic review and meta-analysis of published randomized controlled trials of combination of clopidogrel and aspirin in transient ischemic attack or minor stroke - Zhou, Xingjian (Exp Ther Med, 2017)
The use of antiplatelet agents in patients with ischemic stroke is recommended. In this study, we compared the efficacy and safety of the treatment of clopidogrel plus aspirin (ASA) and that of ASA alone in patients with mild stroke/transient ischemic attack (TIA). Randomized controlled trial (RCT) studies of Clop + ASA vs. ASA therapy in the patients with minor stroke/TIA were identified by electronic bibliographic searches. The primary result was recurrent stroke, while myocardial infarction (MI) as well as vascular mortalities were the secondary result, and major hemorrhagic events were the safety result. A comparative analysis of binary outcomes was performed on the treatment groups, with the employment of fixed effect models and the measurement of risk ratios (95% CI). Five RCT studies involving 9,527 patients were included. Compared with the group with ASA treatment, there was significant reduction in the incidence of recurrent stroke in the group with Clop + ASA (RR=0.76, 95% CI=0.67–0.87, P<0.0001), and there was no significant increase in the incidence of vascular mortalities and MI (RR=1.08, 95% CI=0.83–1.41, P=0.56) and no significant change in major hemorrhagic events (RR=1.55, 95% CI=0.72–3.36, P=0.26). Therefore, the treatment with Clop + ASA seems safe as well as effective for decreasing stroke recurrence. In addition, this is related to a statistically insignificant trend in increasing vascular mortalities, MI, and primary hemorrhagic events. These findings need to be confirmed in prospective studies.